4D Printing at the Microscale. (19th December 2019) - Spiegel, Christoph A.; Hippler, Marc; Münchinger, Alexander; Bastmeyer, Martin; Barner‐Kowollik, Christopher; Wegener, Martin; Blasco, Eva
Abstract: 3D printing of adaptive and dynamic structures, also known as 4D printing, is one of the key challenges in contemporary materials science. The additional dimension refers to the ability of 3D printed structures to change their properties—for example, shape—over time in a controlled fashion as the result of external stimulation. Within the last years, significant efforts have been undertaken in the development of new responsive materials for printing at the macroscale. However, 4D printing at the microscale is still in its early stages. Thus, this progress report will focus on emerging materials for 4D printing at the microscale as well as their challenges and potential applications. Hydrogels and liquid crystalline and composite materials have been identified as the main classes of materials representing the state of the art of the growing field. For each type of material, the challenges and critical barriers in the material design and their performance in 4D microprinting are discussed. Importantly, further necessary strategies are proposed to overcome the limitations of the current approaches and move toward their application in fields such as biomedicine, microrobotics, or optics. Abstract : Toward dynamic microstructures: This progress report focuses on emerging materials for 4D printing at the microscale, with special emphasis on hydrogels and liquid crystalline and composite materials, as well as their challenges and potential applications.